Concepts, signs and classification of measures to ensure criminal proceedings - Lohin, R. I.; Логін, Р. І. (Visegrad journal on human rights. – 2023. – № 6. – P. 119-126, 2023)
У статті проаналізовано сучасні наукові підходи до визначення поняття, особливостей заходів забезпечення кримінального провадження та їх класифікація. Виділено відносини між цим поняттям і поняттям процесуального примусу. Наголошено, що ознаки заходів забезпечення кримінального провадження слід поділяти на загальні та конкретні.

The paper analyzes modern scientific approaches to the definition of the concept, features of measures to ensure criminal proceedings and their classification. The relationship between this concept and the concept of procedural coercion is highlighted. It is emphasized that the signs of measures to ensure criminal proceedings should be divided into general and specific. General (generic) are those that are common to all types of procedural actions, i.e. inherent in other types of procedural actions. Specific or specific - those that are inherent exclusively to the means of ensuring criminal proceedings and allow to feed them from the range of procedural actions of other types. Methodology. During the research, a spectrum of both general scientific and special methods of cognition was applied, in particular, methods of dialectical and formal logic: analysis, synthesis, deduction, induction, comparative, and systemic-structural methods. Results. Emphasis is placed on the existing high degree of scientific development of the concept of measures to ensure criminal proceedings, which can become the foundation for further research of this institute of criminal proceedings, in particular, and in the direction of the peculiarities of their application in criminal proceedings regarding certain types of criminal offenses.

В статье анализируются современные научные подходы к определению понятия, особенностей мер обеспечения уголовного судопроизводства и их классификация.
Keywords: кримінальне провадження; засоби забезпечення кримінального провадження; процесуальний примус; поняття; ознаки; класифікація; criminal proceedings; means of ensuring criminal proceedings; procedural coercion; concepts; signs; classification; уголовное производство; средства обеспечения уголовного судопроизводства; процессуальные принуждение; понятия; признаки; классификация